Current epidemiological and molecular patterns of haemonchosis in Cairo and Giza governorates, Egypt - Noha M. Hassan; Mohamed A. Helal; Bassma S. Elsawy; Eman E. El Shanawany; Nadia M. Abu EL Ezz; Hatem A. Shalaby; Amira H. El Namaky; Omnia M. Kandil; Mona S. Mohamed; Hassan M. Desouky; Emad B. Ata (Iraqi Journal of Veterinary Sciences)
This study explored current epidemiological and molecular patterns of Haemonchus species infecting sheep, particularly in Cairo and Giza governorates, Egypt. Mass screening of haemonchosis was implemented by detecting IgG using ELISA among living sheep reared by smallholder shepherds and via abomasal inspection for sheep at slaughterhouses. Molecular characterization of the adult Haemonchus worms was done through the Nuclear internal transcribed spacer-2 gene (ITS-2) and the mitochondrial cytochrome oxidase-1 gene (COX-1). The results indicated that haemonchosis was a seriously common parasitic infection among sheep, where the prevalence reached 70% for the living sheep and 37.1% for the slaughtered ones. A strong immune response in the abomasal mucosa was detected, with diffuse, multifocal infiltration of lymphocytes, plasma cells, macrophages, and eosinophils. Risk factors significantly linked to the high incidence were being 2 years or less, in autumn, of imported Sudanese breeds, and living in a colder climate. The molecular screening revealed 100% identity of the tested worms as H. contortus, and no H. placei existed. Based on the phylogenetic analysis, the Egyptian Haemonchus isolates of COX-1 sequences showed identity percent ranging from 94.85–99.37%, with previously recorded GenBank isolates from Egypt and Nigeria. However, the isolates of ITS-2 sequences from Egyptian Haemonchus revealed an identity percent of 98.29-99.78%, with those obtained from a small ruminant in Tanzania and a giraffe in Florida, USA. The current data highlighted the considerable risk of haemonchosis among sheep and revealed the importance of updating the epidemiological and molecular information to achieve a suitable preventive and control strategy.